Good Syndrome Occurred in a Patient a Prolonged Time after Thymectomy: A Case Report and Literature Review of Cases in Japan. (27th September 2016) - Nishizawa, Tomotaka; Saraya, Takeshi; Kurai, Daisuke; Sohara, Erei; Tsukahara, Yayoi; Ishii, Haruyuki; Goto, Hajime; Takizawa, Hajime
Abstract : A 70‐year‐old Japanese woman was referred to our hospital with productive cough and recurrent respiratory infections. She underwent a thymectomy nine years previously for a thymoma. Based on a three‐year history of repeated respiratory infections and the presence of hypogammaglobulinemia, a diagnosis of Good syndrome was made. We reviewed forty‐six reported Japanese Good syndrome cases. The most commonly infected sites were the lungs, blood, and digestive tracts. Cases with preceding thymoma required a median time of three years (25th and 75th percentile: 1 and 7 years) until hypogammaglobulinemia emerged. The present case showed that Good syndrome should be considered even after a long time period following thymectomy.